Pengaruh Penilaian Prestasi Pegawai Terhadap Promosi Pegawai pada SMP Negeri 6 Kota Langsa - Agustinawati; Arifin Arahman (Jurnal Ekonomi Manajemen dan Sekretari, 2021)
This study aims to analyze the effect of employee performance appraisal on employee promotions at SMP Negeri 6 Langsa City. The data collection method used a questionnaire given to 50 employees of SMP Negeri 6 Langsa City who had undergone the process of assessing employee performance and promotion. Data were analyzed using multiple linear regression. The results showed that employee performance appraisal had a significant positive effect on employee promotions at SMP Negeri 6 Langsa City. Factors that have a significant effect on employee performance appraisal are work performance, work attitudes, and skills and competencies. While the factors that most influence on the promotion of employees are skills and competencies. Based on the research results, it can be concluded that employee performance appraisal has an important role in determining employee promotions. Therefore, SMP Negeri 6 Langsa City is advised to improve the employee performance appraisal system by taking into account the factors that have a significant influence, as well as providing training and developing skills and competencies for employees to increase opportunities for employee promotion in the future.